2003
DOI: 10.1258/096914103321610789
|View full text |Cite
|
Sign up to set email alerts
|

Original Paper: Does evidence-based information about screening for prostate cancer enhance consumer decision-making? A randomised controlled trial

Abstract: Objectives: Efforts to educate men about the controversy surrounding prostate cancer screening are well intended but rarely evaluated rigorously. We evaluated an evidence-based (EB) booklet for men designed to promote informed decision-making. We also determined whether men's preference for involvement in decision-making ("passive", "collaborative" or "active") modified its impact. Setting and methods: Men aged 40-70 years were recruited from the practices of 13 local general practitioners (GPs) in Sydney, Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(165 citation statements)
references
References 23 publications
(28 reference statements)
4
161
0
Order By: Relevance
“…The outcomes of this study also add to findings from previous studies that have identified the beneficial impact of prostate cancer education materials on patient decisional conflict, knowledge, anxiety, and role in the decision-making process. [9][10][11][12][13][14][15][16][17][18][19][20] However, this study is the first to directly compare patient information on prostate cancer screening delivered through video, internet, and written formats to men previously not screened for prostate cancer, and suggest that media format may not significantly alter these clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of this study also add to findings from previous studies that have identified the beneficial impact of prostate cancer education materials on patient decisional conflict, knowledge, anxiety, and role in the decision-making process. [9][10][11][12][13][14][15][16][17][18][19][20] However, this study is the first to directly compare patient information on prostate cancer screening delivered through video, internet, and written formats to men previously not screened for prostate cancer, and suggest that media format may not significantly alter these clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Both formats have been associated with an increase in patient health knowledge, a shift toward an active or shared decision-making process, a decrease in patient decisional conflict, and a preference to not undergo screening for prostate cancer. [9][10][11][12][13][14][15][16][17][18][19][20] To date, only one study has investigated the effectiveness of the internet as a patient education tool for prostate cancer screening. It compared information delivered via the internet and video and identified increases in patient knowledge and a decrease in patient preference for prostate cancer screening across both interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions that may help correct misperceptions include: having family members present at meetings with doctors to ask additional questions and record information; explaining treatment options and treatmentrelated mortality and outcome estimates a number of times (either through the use of educational materials, particularly interactive educational materials such as CD-ROMs, or through repeat visits with health care personnel and reiteration of estimates); testing patient understanding of these estimates, to verify that informed consent truly has been given; and early involvement of psychiatry and social services, when appropriate. [49][50][51][52][53][54] …”
Section: Discussionmentioning
confidence: 99%
“…Values Clarification Tool-The values clarification tool is a 10-item tool to help men better understand their preferences regarding screening [38]. The 10 items appear throughout the website in the relevant content sections.…”
Section: Methodsmentioning
confidence: 99%